A Parham Cyclization route to the 2, 3-dihydro-1H-indazole-1, 2-dicarboxylate ring systems via condensation of thermolabile aryllithium reagents and azodicarboxylate esters. Issue 19 (10th May 2017) - Farrokh, John; Craven, Timothy; Hunt, David A.
Graphical abstract: Highlights: The Parham reaction can be applied toward the preparation of the 2, 3-dihydro-1 H -indazole-1, 2-dicarboxylate ring system. o -Lithiobenzyl chlorides react with azodicarboxylate esters at low temperature. This provides a new entry to the 2, 3-dihydro-1 H -indazole-1, 2-dicarboxylate ring system. Yields are moderate to good. Abstract: The Parham Cyclization reaction of o -lithiobenzyl chlorides (generated by low temperature halogen-metal exchange of the corresponding o -bromobenzyl chlorides with n -butyllithium) with azodicarboxylate esters provides a new entry to the 2, 3-dihydro-1 H -indazole-1, 2-dicarboxylate ring system in moderate to good yield.